2024
DOI: 10.24084/repqj17.370
|View full text |Cite
|
Sign up to set email alerts
|

Red Macroalgae Kappaphycus alvarezii as feedstock for nutraceuticals, pharmaceuticals and fourth generation biofuel production

Abstract: Biorefineries intends to utilize algal biomass and their by-products at industrial scale. The macroalgae Kappaphycus alvarezii has high content of carrageenan, which is a polysaccharide hydrocolloid, serving as a raw material for the production of third generation biofuels, food and pharmaceuticals. The aim of this study is to show that besides these products, there is the potential for the production of a fourth generation biofuel. Two strains, brown and red, were selected based on their high growth rates and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…Biomass and lipid yield of the same strain of microalgae are also affected by the cultivation process. In this context, genetic modification/metabolic engineering may be promising alternatives to the production of lipid levels and algal biomass [40]. Researchers are searching for an acceptable method of culture to increase lipid content and make it more cost-effective and sustainable.…”
Section: Third and Fourth Generation Biofuelproductionmentioning
confidence: 99%
“…Biomass and lipid yield of the same strain of microalgae are also affected by the cultivation process. In this context, genetic modification/metabolic engineering may be promising alternatives to the production of lipid levels and algal biomass [40]. Researchers are searching for an acceptable method of culture to increase lipid content and make it more cost-effective and sustainable.…”
Section: Third and Fourth Generation Biofuelproductionmentioning
confidence: 99%
“…In challenging situations, the accumulation of lipids leads to cell development and division being stopped, resulting in a clear limitation of the productivity of biomass [62]. Genetic manipulation engineering can deliver innovative routes to lipid and algal biomass production [63]. Through calculation, it was demonstrated that replacing 1% of US road fuel source with macroalgal biofuel only involves 0.09% area of the Exclusive Economic Zone (EEZ) [64].…”
Section: Third-generation Biofuel (3g)mentioning
confidence: 99%